The role of environmental managers in knowledge co-production: Insights from two case studies. Issue 116 (February 2021) - O'Connor, Ruth A.; Nel, Jeanne L.; Roux, Dirk J.; Leach, Joan; Lim-Camacho, Lilly; Medvecky, Fabien; van Kerkhoff, Lorrae; Raman, Sujatha
Highlights: Environmental decision-makers are more diverse than co-production processes acknowledge. Issue definition is science-led, making it hard for environmental managers to contribute. Environmental managers make important and varied knowledge contributions. Environmental managers value science and this influences their participation. Scientist-manager relationships facilitate mutual understanding and use of knowledge. Abstract: Transdisciplinary collaborative processes like knowledge co-production have been promoted as valuable mechanisms to address complex environmental management issues. Their value is based on epistemic and participatory ideals involving academic and non-academic knowledge and values being elicited and deliberated upon. While idealised processes of participation have been described, the actual nature of non-academic contributions including those of environmental managers has received scant attention. We explore the role and input of environmental managers in knowledge co-production, drawing on two cases from Australia and South Africa. We use an analytical frame based on the co-production idiom which focuses on process legitimacy when involving lay participants in science-informed dialogue. Environmental managers tend to be treated as part of a homogeneous group of 'policy-makers' but our research reveals that this characterisation masks individuals with a diversity of motivations, skills and responsibilities who contribute empirical, pragmatic and normative knowledge to co-production. Our results also suggest that environmental managers were not always able to contribute meaningfully to the critical early step of issue definition. These new insights suggest better conceptualisation of decision-maker expertise and roles, and flexibility in design and implementation of collaborative processes, are required if knowledge co-production is to achieve a participatory ideal and substantively better environmental management decisions.